Enhancing Sustainable Environmental Legal Awareness through Legal Education: Penguatan Kesadaran Hukum Lingkungan Berkelanjutan melalui Pendidikan Hukum - Helmi, Helmi; Hafrida, Hafrida; Kusniati, Retno; Rosmidah, Rosmidah; Bustanuddin, Bustanuddin (Mendapo: Journal of Administrative Law, 2025)
This article examines the role of legal education in strengthening sustainable environmental legal awareness amid the increasing complexity of ecological problems and the low level of compliance with environmental protection principles. This study employs a normative juridical approach by analyzing concepts, doctrines, and contemporary paradigms of environmental law in relation to the formation of legal awareness. The findings indicate that the limited effectiveness of environmental protection is not merely caused by weaknesses in legal norms, but is largely influenced by the insufficient internalization of environmental legal values within social consciousness. Legal education holds a strategic position as an instrument for fostering ecological awareness through the understanding of the precautionary principle, social responsibility, intergenerational justice, and sustainability. Through value-oriented and critical legal education, environmental law is not only understood as a set of normative rules, but also as a value system that shapes human behavior and mindset in relation to nature. Therefore, legal education functions as a means of social transformation that promotes behavioral change, strengthens legal compliance, and contributes to the prevention of environmental degradation in a sustainable manner